Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Fashion Pada Aplikasi Shopee Program Studi Pendidikan Ekonomi Universitas HKBP Nommensen Pematang Siantar - Yustika Warni Pardosi; Binsar Tison Gultom; Debbi Ptra Meyana Sitorus (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Current technological developments are increasingly showing very rapid improvements. Technology is increasingly showing progress where all daily activities are carried out easily and quickly, one of which is technological development which is growing rapidly and is currently a trend, namely online trading (e-commerce). The purpose of this research is to determine the influence of product price and quality on purchasing decisions on the Shopee Application, Economic Education Study Program, HKBP Nomensen University, Pematang Siantar. This research is quantitative. The sampling technique used Slovin, a total of 201 people and the measurement scale used a Likert scale. In data analysis using multiple regression tests with the SPSS 21 program. Based on the calculation results, it shows that the price variable partially has an influence on purchasing decisions, namely 4.110, the product quality variable partially has an influence on purchasing decisions of 6.108. Meanwhile, the price and product quality variables simultaneously have an influence on purchasing decisions of 82.971. This means that the better the price and quality of the product, the higher the purchasing decisions will be and thus the level of customer loyalty will increase